Mosquito population structure, pathogen surveillance and insecticide resistance monitoring in urban regions of Crete, Greece. - Emmanouil A Fotakis; Konstantinos Mavridis; Anastasia Kampouraki; Sofia Balaska; Filianna Tanti; George Vlachos; Sandra Gewehr; Spiros Mourelatos; Antonios Papadakis; Maria Kavalou; Dimitrios Nikolakakis; Maria Moisaki; et al. (Public Library of Science (PLoS), 2022)
Background In Greece vector borne diseases (VBD) and foremost West Nile virus (WNV) pose an important threat to public health and the tourist industry, the primary sector of contribution to the national economy. The island of Crete, is one of Greece's major tourist destinations receiving annually over 5 million tourists making regional VBD control both a public health and economic priority. Methodology Under the auspices of the Region of Crete, a systematic integrative surveillance network targeting mosquitoes and associated pathogens was established in Crete for the years 2018-2020. Using conventional and molecular diagnostic tools we investigated the mosquito species composition and population dynamics, pathogen infection occurrences in vector populations and in sentinel chickens, and the insecticide resistance status of the major vector species. Principal findings Important disease vectors were recorded across the island including Culex pipiens, Aedes albopictus, and Anopheles superpictus. Over 75% of the sampled specimens were collected in the western prefectures potentially attributed to the local precipitation patterns, with Cx. pipiens being the most dominant species. Although no pathogens (flaviviruses) were detected in the analysed mosquito specimens, chicken blood serum analyses recorded a 1.7% WNV antibody detection rate in the 2018 samples. Notably detection of the first WNV positive chicken preceded human WNV occurrence in the same region by approximately two weeks. The chitin synthase mutation I1043F (associated with high diflubenzuron resistance) was recorded at an 8% allelic frequency in Lasithi prefecture Cx. pipiens mosquitoes (sampled in 2020) for the first time in Greece. Markedly, Cx. pipiens populations in all four prefectures were found harboring the kdr mutations L1014F/C/S (associated with pyrethroid resistance) at a close to fixation rate, with mutation L1014C being the most commonly found allele (≥74% representation). Voltage gated sodium channel analyses in Ae. albopictus revealed the presence of the kdr mutations F1534C and I1532T (associated with putative mild pyrethroid resistance phenotypes) yet absence of V1016G. Allele F1534C was recorded in all prefectures (at an allelic frequency range of 25-46.6%) while I1532T was detected in populations from Chania, Rethymnon and Heraklion (at frequencies below 7.1%). Finally, no kdr mutations were detected in the Anopheles specimens included in the analyses. Conclusions/significance The findings of our study are of major concern for VBD control in Crete, highlighting (i) the necessity for establishing seasonal integrated entomological/pathogen surveillance programs, supporting the design of targeted vector control responses and; ii) the need for establishing appropriate insecticide resistance management programs ensuring the efficacy and sustainable use of DFB and pyrethroid based products in vector control.